Neutron-neutron correlation in the halo dissociation of light exotic nuclei - Yamashita, Marcelo Takeshi [UNESP]; Frederico, T.; Tomio, L. (American Physical Soc, 2005)
We present model results for the two-halo-neutron correlation functions, C-nn, for the dissociation process of light exotic nuclei modelled as two neutrons and a core. A minimum is predicted for C-nn as a function of the relative momentum of the two neutrons, p(nn), due to the coherence of the neutrons in the halo and final state interaction. Studying the systems Be-14, Li-11, and He-6 within this model, we show that the numerical asymptotic limit, C-nn-> 1, occurs only for p(nn)greater than or similar to 400 MeV/c, while such limit is reached for much lower values of p(nn) in an independent particle model as the one used in the analysis of recent experimental data. Our model is consistent with data once the experimental correlation function is appropriately normalized.